Implementation of automated dispensing cabinets for management of medical devices in an intensive care unit: organisational and financial impact. Issue 2 (8th September 2015) - Bourcier, Elsa; Madelaine, Sophie; Archer, Valérie; Kramp, François; Paul, Muriel; Astier, Alain
Abstract : Background: Automated dispensing cabinets (ADCs) have been tested and approved for medication management in hospitals. Objectives: First, to evaluate the logistics and organisational effect of a similar system for management of sterile medical devices in a medical intensive care unit (ICU). Second, to assess the cost savings of this new organisation for the sterile medical devices budget of this department. Methods: The organisational effect was evaluated by comparing (1) the workload of head nurse, nursing auxiliary and pharmacy technician and (2) sterile medical devices emergency orders, 1 year before and after implementation of three ADCs and 100 wireless open-access devices. The hospital's costs (ADC, wireless devices and software) and benefits (stock value and resupplying value before and after implementation) were evaluated. Results: Employment of ADCs led to organisational improvement: the total time saved by the pharmacy and ICU together was 34% of the time spent before introduction. The number of emergency orders decreased from 6% to 1% of total orders after 1 year. €55 000 were saved (stock value + resupplying value) 1 year after introduction of ADCs. These benefits were almost equal to the cost of introducing the system. Conclusions: ADCs could provide an innovative and efficient solution for the management of sterile medical devices in hospitals. Further investigations are needed to complete the financial evaluation, and to develop this system to provide a secure a medical devices circuit.